Respuesta :

Mxnixc

Answer: it’s A

Step-by-step explanation: I got it right, hope it helps ✨

The value of the expression  [tex](\frac{3^{2}a^{-2} }{3a^{-1} } )^{k}[/tex] when a = 5 and k = -2 is [tex]\frac{25}{9}[/tex]

How to substitute and get the value of an expression?

The expression is as follows:

[tex](\frac{3^{2}a^{-2} }{3a^{-1} } )^{k}[/tex]

using law of indices

Hence,

when a = 5, k = -2

[tex](\frac{3^{2}a^{-2} }{3a^{-1} } )^{k} = (\frac{9(5^{-2} )}{3(5^{-1} )})^{-2}[/tex]

Then,

[tex](\frac{9(5^{-2} )}{3(5^{-1} )})^{-2}=(\frac{\frac{9}{25} }{\frac{3}{5} } )^{-2}[/tex]

[tex](\frac{\frac{9}{25} }{\frac{3}{5} } )^{-2}=(\frac{9}{25} (\frac{5}{3}))^{-2}[/tex]

[tex](\frac{9}{25} (\frac{5}{3}))^{-2}=(\frac{3}{5})^{-2}[/tex]

[tex](\frac{3}{5})^{-2}=\frac{25}{9}[/tex]

Therefore, the value of the expression is 25 / 9

learn more on expression here:https://brainly.com/question/12879207

#SPJ5

Ver imagen vintechnology